Network Security Monitoring System Via Notification Alert - Rachmat Muwardi; Hongmin Gao; Harun Usman Ghifarsyam; Mirna Yunita; Andika Arrizki; Julpri Andika (Journal of Integrated and Advanced Engineering (JIAE), 2021)
The development of information technology nowadays has become faster, and this makes network security become important. A huge increasing number of computers that are connected makes many gaps in a network. An administrator has an important role in protecting the security of the network. The problem comes when an administrator has human problems such as pain, negligence, and tiredness while needing rapid information when there is an intrusion on the network. This problem can be solved by adding a data traffic detection system known as Intrusion Detection System (IDS). IDS will be connected to Mail Gateway until that administrator can receive notifications such as alerts during an intrusion to the network anytime and anywhere. Snort as one of the network security systems should be developed as a security detection system and network security. A security intrusion prevention system or an Intrusion Prevented System (IPS). The author tries to do analysis and testing on the subjects above to produce a system capable of detecting the intruder in a network that is mobile and also makes it easy for administrators to open data anywhere and anytime using any device.